2009
DOI: 10.1016/s1726-4901(09)70413-7
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Tension Pneumothorax and Tension Pneumoperitoneum Secondary to Tracheal Tear in a Patient With Relapsing Polychondritis

Abstract: Relapsing polychondritis (RP) is a rare disease that is characterized by recurrent inflammation and destruction of cartilage and connective tissues. RP can have significant airway pathology that may require procedures to maintain airway patency and thus may have serious implications for anesthesiologists. Anesthesiologists must be prepared to deal with the possible complications that may occur during airway manipulation in patients with RP. Here, we present a case of life-threatening bilateral tension pneumoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Karamen et al [98] described surgical reconstruction of the laryngotracheal region in three patients with extensive respiratory involvement. A case of life-threatening bilateral tension pneumothorax and tension pneumoperitoneum that developed after a tracheal tear during Montgomery T-tube insertion in a patient with tracheal stenosis due to RP has been described [99]. Childs et al [100] reported the use of pulsedpotassium-titanyl-phosphate laser for the management of bilateral bamboo nodules of the vocal folds associated with RP.…”
Section: Managementmentioning
confidence: 99%
“…Karamen et al [98] described surgical reconstruction of the laryngotracheal region in three patients with extensive respiratory involvement. A case of life-threatening bilateral tension pneumothorax and tension pneumoperitoneum that developed after a tracheal tear during Montgomery T-tube insertion in a patient with tracheal stenosis due to RP has been described [99]. Childs et al [100] reported the use of pulsedpotassium-titanyl-phosphate laser for the management of bilateral bamboo nodules of the vocal folds associated with RP.…”
Section: Managementmentioning
confidence: 99%
“…[3] So, the resulting bilateral pneumothorax can occur as a sudden catastrophe immediately following emergency tracheostomy or acute tracheal obstruction. [4,[7][8][9] In our patient long-standing airway obstruction with marked negative intra-thoracic pressure, fibrosis of the neck tissues with difficult dissection to expose trachea and extension of neck may have led to this complication. Negative pressure pulmonary edema can also occur with forced inspiration against a closed or obstructed airway.…”
Section: Discussionmentioning
confidence: 74%
“…[5] There are few reports of its occurrence following surgical tracheostomy (ST). [2,4,[6][7][8][9] Cases have also been reported following PDT. [10] The mechanism for its occurrence after tracheotomies, as suggested by Padovan and coworkers, involves the entry of air through the cervical incision and its downward passage peritracheally into the mediastinum during inspiration, presumably due to the drop in pleural pressure which accompanies inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Most important thing in stent placement is choosing the location at which the stents will do the most good [10]. However, in case of diffuse involvement, as in this patient, the effect of stenting would not outweigh the risk of complications [11]. …”
Section: Discussionmentioning
confidence: 99%